Synthesis of chromene derivatives using microwave-assisted method - Thanh Mai, Nguyen Thi; Hong Nhung, Le Thi (Vietnam Journal of Chemistry, 2016)
Eleven new chromens have been synthesized by condensation reaction of some amines with 6-butoxy-2-oxo-2H-chromene-4-carbaldehyde 4 or 3-acetyl-6-substituted-2H-chromene-2-one 7 under microwave irradiation. This method offers several advantages: fast reaction rates and significantly high yields. The products were equally available and their structures were confirmed by IR, 1H-and 13C-NMR spectral data. Antimicrobial activities of the obtained compounds have been tested. The results showed that they possess remarkable antimicrobial activities  against Candida albicans. Keywords. Chromene; solvent-free; microwave-assisted method.